Regularity in generalized Morrey spaces of solutions to higher order nondivergence elliptic equations with VMO coefficients - Tahir Gadjiev; Shahla Galandarova; Vagif Guliyev (Electronic Journal of Qualitative Theory of Differential Equations, 2019)
We study the boundedness of the sublinear integral operators generated by Calderón–Zygmund operator and their commutators with $BMO$ functions on generalized Morrey spaces. These obtained estimates are used to get regularity of the solution of Dirichlet problem for higher order linear elliptic operators.